Auditors' application of materiality: insight from the UK. Issue 1 (2nd January 2023) - Quick, Reiner; Zaman, Mahbub; Mandalawattha, Gihani
ABSTRACT: Changes to the auditors' reports aim to reduce the information gap and make auditing more transparent. Despite the existence of standards and guidelines research on materiality in practice is limited, this article examines auditors' application of materiality as disclosed in their reports following the introduction of the revised standard on auditors' reports in the UK. We provide evidence on actual benchmarks used and materiality rationales. Additionally, we also examine audit firm and industry variations in materiality practices as well as materiality reporting to audit committees. We find materiality disclosures are generally compliant with regulation and consistent with a desire to reduce the information gap auditors make additional disclosures. However, there is variation in the nature and extent of disclosures, possibly due to potential concerns about making the subjectivity of auditing too apparent, which can limit the reports' usefulness. Overall, the revised standard has enhanced transparency, but there is room for improvement in providing more meaningful disclosures in the auditors' reports.